Pengaruh Pemahaman Standar Akuntansi Pemerintah, Pengalaman Kerja Dan Pemanfaatan Sistem Informasi Akuntansi Terhadap Kualitas Laporan Keuangan Pemerintah Daerah ( Studi Empiris Pada Dinas Pendapatan Pengelolaan Dan Aset Daerah Kabupaten Sukoharjo) - Yuliana, Linna; , Dra. Nursiam, M.H., Ak., CA (2016)
This study aimed to analyze the effect of government understanding of accounting standards, work experience and utilization of accounting information system of the quality of financial statements of Local Government. This type of research is associative research with quantitative approach. The population in this study were employees of financial management at the Department of Finance and Asset Management Revenue Regional Government of Sukoharjo district. A sample of 40 employees obtained by using convenience sampling method. The method used in this study using a quantitative method with multiple linear regression using SPSS version 17 to test the hypothesis. The results of this study showed that simultaneous and partial understanding of the variables government accounting standards, work experience and utilization of accounting information systems affect the quality of financial reporting.